#BlackGirlMagic: The identity conceptualization of Black women in undergraduate STEM education. Issue 6 (29th September 2018) - Morton, Terrell R.; Parsons, Eileen C.
Abstract: Much of the research in science education that explores the influence of a racial and gendered identity on science, technology, engineering, and mathematics (STEM) engagement for Black women situate their identities primarily as responses to the oppression and struggles they face in STEM. In this study, we use Phenomenological Variant Ecological Systems Theory as a strengths‐based approach to investigate 10 undergraduate Black women's perceptions of race and gender on their STEM identity development and engagement. The qualitative analysis of interview and journal data revealed these women enter STEM experiences cognizant of their race and gender identities, naming them in isolation and intersectionally as a potential risk or as being protective, positive, and empowering for their STEM engagement. These findings illuminate the importance of Black women self‐authoring their identities in STEM contexts, both in naming what is salient and defining what those names mean, and have implications for STEM retention and matriculation efforts.